The Use of Health Technology to Enhance the Adherence of Tuberculosis Treatment: A Systematic Review - Dwi Uswatun Sholikhah; Gevi Melliya Sari; Cahya Mustika Narendri; Sariati Sariati; Nora Dwi Purwanti (Jurnal Ners, 2019)
Introduction: Disobedience in the context of TB treatment is one of the major problems around the world. Many efforts have been made to improve the adherence to TB treatment; one of them is the utilization of health technology such as digital technology. The aim of the study was to identify the effectiveness of the use of health technology such as digital technology to improve treatment compliance.Methods: The literature review was used to identify the interventions and then the identification of the relevant literature was done by topic and title, obtaining the literature in full text form. The analysis of the results was drawn from the many interventions in the literature. There were 15 articles found from the systematic search performed in the Scopus, Proquest, Science direct, Spingerlink and Sage databases with an RCTs design. This was conducting by entering the keywords of adherence, promoting adherence, improving adherence, tuberculosis treatment, chronic disease, health technology, digital technology, mhealth and self-reminders.Results: The search was limited to journals from 2013 to 2018, with the inclusion criteria being the use health technology such as digital technology to improve the adherence to chronic disease treatment (TB treatment).Conclusion: There are several uses of health technology when it comes to improving the adherence to TB treatment that can be used as a promotive and preventive effort during the treatment of TB.